2014
DOI: 10.1002/jbm.b.33292
|View full text |Cite
|
Sign up to set email alerts
|

In vivo monitoring of rat macrophages labeled with poly(l‐lysine)‐iron oxide nanoparticles

Abstract: Coprecipitation of FeCl2 and FeCl3 with aqueous ammonia was used to prepare iron oxide nanoparticles dispersible in aqueous medium. Oxidation of the particles with sodium hypochlorite then yielded maghemite (γ-Fe2 O3 ) nanoparticles which were coated with two types of coating -d-mannose or poly(l-lysine) (PLL) as confirmed by FTIR analysis. The particles were <10 nm according to transmission electron microscopy. Their hydrodynamic particle size was ∼180 nm (by dynamic light scattering). The d-mannose-, PLL-coa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 37 publications
(37 reference statements)
0
5
0
Order By: Relevance
“…NSCs have a great potency to regenerate the central nervous system, and are often used as cells of choice in brain applications [23]. Despite a prior positive experience of using PLL-γ-Fe 2 O 3 nanoparticles for cell labeling [22], the detailed analysis on biocompatibility of PLL-γ-Fe 2 O 3 nanoparticles was not described, neither the method of nanoparticle cell uptake defined.…”
Section: Discussionmentioning
confidence: 99%
“…NSCs have a great potency to regenerate the central nervous system, and are often used as cells of choice in brain applications [23]. Despite a prior positive experience of using PLL-γ-Fe 2 O 3 nanoparticles for cell labeling [22], the detailed analysis on biocompatibility of PLL-γ-Fe 2 O 3 nanoparticles was not described, neither the method of nanoparticle cell uptake defined.…”
Section: Discussionmentioning
confidence: 99%
“…7 Various chemicals have been used to enhance cellular uptake of NPs, including poly-l-lysine (PLL), which is also applied to gene delivery [8][9][10] and cell labeling. [11][12][13][14] The addition of PLL to cultures enhances NP internalization by stem cells 15,16 and tumor cells. 16,17 PLL coating of NPs undergoes similar uptake enhancement in a variety of cells.…”
Section: Introductionmentioning
confidence: 99%
“…Our results indicated that both free and immobilized PLL greatly enhanced MNP uptake by glioma cells, which is consistent with previous findings that PLL enhanced NP internalization by stem cells 13,[15][16][17]19 and other cells. 11,14,[16][17][18]21 TEM results demonstrated microvilli formation associated with MNP internalization, suggesting that endocytosis may involve macropinocytosis, 20 which is usually the internalization pathway of particles .200 nm. 46 In our study, the number of internalized PLL-MNPs was much lower than Dex-MNPs with PLL in the culture medium, which was probably due to the smaller quantity of immobilized PLL.…”
mentioning
confidence: 99%
“…11,12 The magnetic media is the key factor for magnetic hyperthermia, which includes magnetic nanoparticles, magnetic uid and ferromagnetic thermoseeds. 13,14 For magnetic uid or magnetic nanoparticles, it is difficult to selectively accumulate in tumor tissue 15,16 and can easily leak into the surrounding tissues or blood vessel, which might cause potential safety problems and decrease the therapy efficiency. Ferromagnetic thermoseeds need precision and are relatively big, complex calculating and controlling.…”
Section: Introductionmentioning
confidence: 99%